2015
DOI: 10.1073/pnas.1501124112
|View full text |Cite
|
Sign up to set email alerts
|

Multiplexed metagenome mining using short DNA sequence tags facilitates targeted discovery of epoxyketone proteasome inhibitors

Abstract: In molecular evolutionary analyses, short DNA sequences are used to infer phylogenetic relationships among species. Here we apply this principle to the study of bacterial biosynthesis, enabling the targeted isolation of previously unidentified natural products directly from complex metagenomes. Our approach uses short natural product sequence tags derived from conserved biosynthetic motifs to profile biosynthetic diversity in the environment and then guide the recovery of gene clusters from metagenomic librari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
109
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 105 publications
(114 citation statements)
references
References 30 publications
1
109
0
Order By: Relevance
“…We have shown eSNaPD classification to be a robust indicator of a functional relationship between a microbiome-derived gene cluster yielding an AD or KS domain sequence tag and a curated known gene cluster (20)(21)(22). Based on empirical data from previous metagenomic analyses (20)(21)(22)(23), the homology cutoffs used in this study (e value < 10 −100 ) will identify gene clusters with a high likelihood of encoding either the same metabolite or a novel derivative (congener) of the metabolite encoded by the matching curated gene cluster.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have shown eSNaPD classification to be a robust indicator of a functional relationship between a microbiome-derived gene cluster yielding an AD or KS domain sequence tag and a curated known gene cluster (20)(21)(22). Based on empirical data from previous metagenomic analyses (20)(21)(22)(23), the homology cutoffs used in this study (e value < 10 −100 ) will identify gene clusters with a high likelihood of encoding either the same metabolite or a novel derivative (congener) of the metabolite encoded by the matching curated gene cluster.…”
Section: Resultsmentioning
confidence: 99%
“…AD and KS amplicons were assigned to known biosynthetic gene clusters using the eSNaPD program (18,19). Empirical exploration with the eSNaPD algorithm has shown that e values as high as 10 −40 to −60 return reliable gene cluster predictions (20)(21)(22). We used an expectation value to 10 −100 for this analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Five studies also chose to use shotgun metagenomic methods, which do not require the use of DNA primers, to identify prokaryote DNA from metagenomes (not shown in Fig. 6; Delmont et al 2011;Nakai et al 2011;Inskeep et al 2013;Costa et al 2015;Owen et al 2015).…”
Section: Summary Of Gene Regions Used In Prior Analyses Of Environmenmentioning
confidence: 99%
“…Genome mining is a process in which molecules are discovered by predicting what compound will be biosynthesized based on the sequences of gene clusters. Interpretation of NP-encoding genes and their organization can predict new pathways for discovery of silent or ‘cryptic’ biosynthetic gene clusters 128, 132, 186188 . Combining the developments in tandem MS methods enable one to correlate the production of NPs with the genomic capacity of the microorganism in query or in an interactive complex sample.…”
Section: Studying the Microbial Metabolome With Mass Spectrometry mentioning
confidence: 99%